Automatic Identification of Close Languages – Case Study: Malay and Indonesian. - Bali, Ranaivo-Malançon (2006)
Identifying the language of an unknown text is not a new problem but what is new is the task of identifying close languages. Malay and Indonesian as many other language€ are very similar, and therefore it is a real difficulty to search, retrieve, classify, and above all translate texts written in one of the two Identifying the language of an unknown text is not a new problem but what is new is the task of identifying close languages. Malay and Indonesian as many other language€ are very similar, and therefore it is a real difficulty to search, retrieve, classify, and above all translate texts written in one of the two languages.